Microsatellite-stable diploid carcinoma: a biologically distinct and aggressive subset of sporadic colorectal cancer. - Hawkins, N; Tomlinson, I; Meagher, A; Ward, R (2001)
Chromosomal instability and microsatellite instability represent the major pathways for colorectal cancer (CRC) progression. However, a significant percentage of CRC shows neither pattern of instability, and thus represents a potentially distinctive form of the disease. Flow cytometry was used to determine the degree of DNA aneuploidy in 46 consecutive sporadic colorectal cancers. Microsatellite status was determined by PCR amplification using standard markers, while immunostaining was used to examine the expression of p53. K- ras status was determined by restriction-mediated PCR assay. Twenty-five (54%) tumours were aneuploid, 14 (30%) were diploid and microsatellite-stable and seven (15%) were diploid and microsatellite-unstable. Tumours with microsatellite instability were more likely to be right sided, to occur in women and to be associated with an improved survival. Aneuploid tumours were significantly more common in men and were likely to be left sided. The diploid microsatellite-stable (MSS) tumours did not show a sex or site predilection, but were strongly associated with the presence of metastatic disease at the time of diagnosis. Our data suggests that diploid, MSS tumours represent a biologically and phenotypically distinct subset of colorectal carcinoma, and one that is associated with the early development of metastases. We suggest that the genetic stability that characterizes these tumours may favour the maintenance of an invasive phenotype, and thus facilitate disease progression. These findings may have important implications for treatment options in this disease subset.